DENDA ZAKAT SEBAGAI HUKUMAN TAZIR - Muammar Arafat Yusmad (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
Zakat is an obligation for every Moslem that can do it as written in Surah At-Taubah (9 :103) Take, (O, Muhammad), from their wealth a charity by which you purify them and cause them to increase, and invoke (Allah s blessings) upon them. Indeed, your invocations are reassurance for them. And Allah is Hearing and Knowing. Right now, zakat is an obligation for every Moslem, besides to purify wealth and soul, zakat is also a potential fund source to welfare purpose, social justice, to improve life quality of dhuafa people, and also as one of the resources to national development. As we know, regulation in Indonesia including local regulation is a reception Islamic Law. So, its so clear that there is a connection between Islamic Law and National Law and no exception for regulation of zakat that define Muzakki Fine as a form of punishment of Tazir.